2008
DOI: 10.1111/j.1601-0825.2007.01400.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of sCD14 levels in saliva obtained from patients with various periodontal conditions

Abstract: The findings of the present study reemphasize the importance of whole saliva as sampling method in terms of immunological purposes in periodontal disease and suggest that the elevated sCD14 concentration may be one of the host-response components associated with the clinical manifestations of periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 52 publications
3
25
0
Order By: Relevance
“…Following previous described methods (Isaza‐Guzmán, Aristizábal‐Cardona, Martínez‐Pabón, Velásquez‐Echeverri, & Tobón‐Arroyave, ), ~5 ml of unstimulated whole saliva were collected from each participant by spitting into sterile plastic centrifuge tube (Falcon, Corning Science Mexico SA de CV, Tamaulipas, Mexico). Saliva was collected from participants with overnight fasting (8–12 hr) and without any oral hygiene procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Following previous described methods (Isaza‐Guzmán, Aristizábal‐Cardona, Martínez‐Pabón, Velásquez‐Echeverri, & Tobón‐Arroyave, ), ~5 ml of unstimulated whole saliva were collected from each participant by spitting into sterile plastic centrifuge tube (Falcon, Corning Science Mexico SA de CV, Tamaulipas, Mexico). Saliva was collected from participants with overnight fasting (8–12 hr) and without any oral hygiene procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, there is evidence from 2 independent studies that levels of salivary soluble CD14 (sCD14) are elevated in periodontitis [87, 91]; sCD14 mediates the action of LPS and may promote bacterial invasion of host cells in periodontitis [92, 93]. Also, although salivary sTLR2 augments IL-8 (CXCL8) production in monocytes [94], there is evidence for diminished levels of sTLR2 in periodontitis saliva [87].…”
Section: Protein Biomarkers Of Periodontitis: Candidate Protein Stmentioning
confidence: 99%
“…For example, antibodies to Aggregatibacter actinomycetemcomitans (a periodontal pathogen often associated with aggressive periodontitis) and Porphyromonas gingivalis are thought to have a key role in protective immunity in aggressive periodontitis [140] but although these antibodies are indeed found in saliva their presence is not specific to aggressive periodontitis [141, 142]. A very limited number of studies (of comparatively few patients) have directly compared levels of mediators in aggressive periodontitis and chronic periodontitis [91, 127, 143]; with the exception of one study which reported elevated cathepsin C activity in the saliva of aggressive periodontitis patients [143] none of these studies have identified biomarkers which might be potentially specific for aggressive periodontitis. Although there is a real need for larger studies, establishing specific protein biomarkers may be challenging as there is no evidence for significant differences in the immunopathogenesis of these two clinical manifestations of periodontitis [139].…”
Section: Protein Biomarkers Of Periodontitis: Candidate Protein Stmentioning
confidence: 99%
“…The soluble form (sCD14), spontaneously released by these cells, circulates in the serum in high amounts (2-4 µg mL -1 ) and interacts with the LPS-binding protein (LBP) (9). The LPS/LBP/CD14 ternary complex interacts with TLRs, which leads to cell activation (10). Gingival epithelial cells, which are the first to encounter periodontal pathogens, express mostly TLRs.…”
mentioning
confidence: 99%